2022
DOI: 10.3390/agriculture12111850
|View full text |Cite
|
Sign up to set email alerts
|

China and Countries along the “Belt and Road”: Agricultural Trade Volatility Decomposition and Food Security

Abstract: Agricultural products are essential for human survival, and strengthening agricultural trade cooperation between China and countries along the “Belt and Road” (B&R) can promote food security, but there are few studies on bilateral trade fluctuation factors in the literature. This paper uses the modified multi-country multi-product CMS (constant market share) model and the two-country multi-product CMS model to decompose the fluctuation of agricultural trade between China and B&R countries by stage, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This paper measures the carbon emission coefficients of different energy sources using Model (1). According to the energy index data in Table 3, the carbon emission coefficients of kerosene, diesel oil, and fuel oil are high, above 3.0, and fuel oil reaches more than 3.20, while the carbon emission coefficient of coal is the smallest, typically less than 2.0; and the carbon emission coefficients of coke, gasoline, and natural gas are in the range of 2.0-3.0.…”
Section: Direct Carbon Emission Factor For Agricultural Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper measures the carbon emission coefficients of different energy sources using Model (1). According to the energy index data in Table 3, the carbon emission coefficients of kerosene, diesel oil, and fuel oil are high, above 3.0, and fuel oil reaches more than 3.20, while the carbon emission coefficient of coal is the smallest, typically less than 2.0; and the carbon emission coefficients of coke, gasoline, and natural gas are in the range of 2.0-3.0.…”
Section: Direct Carbon Emission Factor For Agricultural Productsmentioning
confidence: 99%
“…As the ties between China and Russia deepen, their collaboration in trade, particularly in agriculture, has witnessed significant growth [1]. Both nations, being major players in the global agricultural market, have strengthened their trade relations due to factors like their entry into the World Trade Organization, the initiation of the Belt and Road Initiative, and economic sanctions imposed by Western countries on Russia [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constant market share (CMS) model, proposed by Tyszynski (1951) and improved by many scholars, is widely used for examining the effect of trade growth in the international trade market and policy research [45]. In recent years, the CMS model has been utilized by researchers to analyze growth factors for the trade of agricultural products in China [46][47][48][49][50]. The basic assumption of the CMS model is that a country's share of exports in the target market will remain unchanged if its competitiveness remains unchanged.…”
Section: Modeling Of Trade Growth Effectsmentioning
confidence: 99%
“…Existing research mainly examines the factors affecting supply and demand in the micro dimension. Some scholars have analyzed grain trade using the constant market share model (CMS), pointing out that the import gravitational and structural effects are the two main elements affecting grain imports [20,21]. Along this line, Scholars have confirmed that the information available to both sides of the trade, bargaining power, the scale of import demand, the growth rate of supply, labor costs and production costs are important factors affecting the fluctuation of grain trade [22,23].…”
Section: Study On Factors Affecting Food Tradementioning
confidence: 99%